Effects of Stress Management Program on Elderly Nursing Skills of Nursing Students - Panichjaroennan, Sakun; Laochai, Wiwat; Rattanapanyakorn, Farkjit; Duangmanee, Dussadee (Journal of The Royal Thai Army Nurses, 2024)
This research was a quasi-experimental study with a one-group pretest-posttest design to compare the stress management and elderly nursing skill scores of nursing students before and after participating in a stress management program. The sample group consisted of 38 second-year nursing students at Suan Dusit University, selected specifically. Data were collected using the elderly nursing skill and stress management questionnaires, with content validity indices of.87 and.90, respectively. The reliability of these instruments was 0.85. and 0.89, respectively. The data were analyzed using frequency, percentage, mean, standard deviation, and paired t-test statistics. The results showed that after participating in the stress management program, the participants had significantly higher elderly nursing skills and stress management mean scores compared to the baseline (p< 0.05). These findings indicate that the stress management program can serve as a guideline for stress management among students, helping to increase their ability to review knowledge and practice of elderly nursing before practicing nursing in the elderly. This can effectively help in reducing stress and enhancing elderly nursing skills among nursing students.